2008
DOI: 10.1242/dev.012708
|View full text |Cite
|
Sign up to set email alerts
|

Recombinase-mediated cassette exchange reveals the selective use of Gq/G11-dependent and -independent endothelin 1/endothelin type A receptor signaling in pharyngeal arch development

Abstract: The endothelin (Edn) system comprises three ligands (Edn1, Edn2 and Edn3) and their G-protein-coupled type A (Ednra) and type B (Ednrb) receptors. During embryogenesis, the Edn1/Ednra signaling is thought to regulate the dorsoventral axis patterning of pharyngeal arches via Dlx5/Dlx6 upregulation. To further clarify the underlying mechanism, we have established mice in which gene cassettes can be efficiently knocked-in into the Ednra locus using recombinase-mediated cassette exchange (RMCE) based on the Cre-lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
60
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 49 publications
(65 citation statements)
references
References 56 publications
5
60
0
Order By: Relevance
“…S10). Ednra expression, mimicked by knocked-in EGFP expression 18,24 , was detected broadly in cardiomyocytes and aortic SMCs, and also in Wnt1-Cre-labelled cells in the condensed mesenchyme and close to the endocardium at E12.5 ( Fig. 5d-f).…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…S10). Ednra expression, mimicked by knocked-in EGFP expression 18,24 , was detected broadly in cardiomyocytes and aortic SMCs, and also in Wnt1-Cre-labelled cells in the condensed mesenchyme and close to the endocardium at E12.5 ( Fig. 5d-f).…”
Section: Resultsmentioning
confidence: 93%
“…The similarity of the Edn1-/Ednra-null phenotype in mouse to the NC ablation in chick suggests that the preotic NC is the target of Edn signalling in coronary remodelling. We have previously reported that Edn1 activates the G-protein-coupled receptor Ednra on preotic NCCs migrating into the first PA, and specifies mandibular identity through G q /G 11 -dependent signalling 18 . This and the present findings indicate that Edn1 activates different signalling and genetic programmes in preotic NCCs in different contexts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, we cannot appreciate the phenotypic consequences of reduced gene expression; third we may fail to recognize the dynamics of cell-cell signaling and interactions, as these often require a nearly normal context. Such is the case of Edn1?Dlx signaling at the basis of the homeotic lower jaw transformation, to investigate which many studies have been carried out based on either loss-of-function (Acampora et al, 1999;Beverdam et al, 2002;Clouthier et al, 1998;Depew et al, 1999Depew et al, , 2002Kurihara et al, 1994;Ozeki et al, 2004;Sato et al, 2008a;Thomas et al, 1998;Yanagisawa et al, 2003) or gain-of-function mutants (Sato et al, 2008b). Here we provide quantitative data on the effects of allelic reduction of Edn1 and Dlx5;Dlx6 at different developmental stages.…”
Section: Discussionmentioning
confidence: 99%
“…The craniofacial and cardiovascular anomalies are attributed to the disordered development of cranial (preotic) and cardiac (postotic) NCCs, respectively. In craniofacial development, the Edn1-Ednra signaling activates Gα q -/Gα 11 -dependent pathway, resulting in the induction of Dlx5/ Dlx6, homeobox genes critical to ventral (mandibular) identity of the pharyngeal arches [10][11][12]. In cardiovascular development, the Edn1-/Ednra-null phenotype of aortic arch anomalies is independent of Dlx5/Dlx6 [13], indicating that the Edn1-Ednra signaling pathway appears differently involved in craniofacial and cardiac development.…”
Section: Endothelin Signal and Neural Crest Developmentmentioning
confidence: 99%